Small molecule quercetin binds MALAT1 triplex and modulates its cellular function - Rakheja, Isha; Ansari, Asgar Hussain; Ray, Arjun; Joshi, Dheeraj Chandra; Maiti, Souvi (Molecular Therapy-Nucleic Acids, 2022)
The triple-helix structure at the 30 end of metastasis-associated lung adenocarcinoma transcript 1 (MALAT1), a long non -cod-ing RNA, has been considered to be a target for modulating the oncogenic functions of MALAT1. This study examines the binding of quercetin-a known triplex binding molecule-to the MALAT1 triplex. By employing UV-visible spectroscopy, circular dichroism spectroscopy, and isothermal titration calo-rimetry, we observed that quercetin binds to the MALAT1 triplex with a stoichiometry of 1:1 and Kd of 495 +/- 61 nM, along with a negative change in free energy, indicating a spontaneous interaction. Employing real-time PCR measurements, we observed around 50% downregulation of MALAT1 transcript levels in MCF7 cells, and fluorescence in situ hybridization (FISH) experiments showed concomitantly reduced levels of MALAT1 in nuclear speckles. This interaction is likely a result of a direct interaction between the molecule and the RNA, as indicated by a transcription-stop experiment. Further, tran-scriptome-wide analysis of alternative splicing changes induced by quercetin revealed modulation of MALAT1 downstream genes. Collectively, our study shows that quercetin strongly binds to the MALAT1 triplex and modulates its functions. It can thus be used as a scaffold for further development of ther-apeutics or as a chemical tool to understand MALAT1 func-tions.

Design and synthesis of photocrosslinker and light blocker based on L-Amino acid polyester and their application in solvent-free resin formulation for DLP/SLA 3D printing - Kamble, Ganesh N.; Joshi, Dheeraj Chandra; Asha, S. K. (Polymers, 2023)
Customising material design for new technological applications like additive manufacturing (AM) is a challenging yet promising approach to create a palette of materials suitable for developing eco-friendly products. LGlutamic acid and L-aspartic acid based aliphatic, photocurable polyester crosslinkers were designed and developed and incorporated into a solvent-free photocurable resin formulation with hydroxyl (ethyl)methacrylate (HEMA). Proof-of-concept 3D printing of clear and transparent objects was demonstrated using digital light processing (DLP) and Stereolithography (SLA) techniques. Resolution of the 3D printed objects could be improved by incorporating a Dansyl labelled L-glutamic acid polyester, which not only aided in modulating the viscosity of the resin formulation but could also function as a light blocker, thereby avoiding polymerization of unwanted areas while 3D printing. The curing kinetics of the photocurable formulation was analyzed using photo differential Scanning Calorimetry. Enzymatic degradability studies of 3D printed films were undertaken in PBS buffer containing esterase enzyme and compared with 3D printed samples using HEMA and a commercial crosslinker (Trimethylolpropane triacrylate (TMPTA)). Scanning electron microscopy (SEM) was used to evaluate the morphology of the 3D printed films before and after enzymatic degradation in the PBS buffer for 60 days. The 3D printed amino acid crosslinked films of HEMA presented high degree of degradation in contrast to the near total absence of any degradation in the 3D printed film crosslinked using TMPTA. The availability of new photocurable formulations that are enzymatically degradable are highly sought after for 3D printing applications.
Keywords: 3D printing; Crosslinker; L -Amino acid Polyester; Light blocker; Photocurable

Identification of G-quadruplex structures in MALAT1 lncRNA that interact with nucleolin and nucleophosmin - Ghosh, Arpita; Pandey, Satya Prakash; Joshi, Dheeraj Chandra; Rana, Priya; Ansari, Asgar Hussain; Sundar, Jennifer Seematti; Singh, Praveen; Khan, Yasmeen; Ekka, Mary Krishna; Chakraborty, Debojyoti; Maiti, Souvik (Nucleic Acids Research, 2023)
Nuclear-retained long non-coding RNAs (lncRNAs) including MALAT1 have emerged as critical regulators of many molecular processes including transcription, alternative splicing and chromatin organization. Here, we report the presence of three conserved and thermodynamically stable RNA G-quadruplexes (rG4s) located in the 3 & PRIME; region of MALAT1. Using rG4 domain-specific RNA pull-down followed by mass spectrometry and RNA immunoprecipitation, we demonstrated that the MALAT1 rG4 structures are specifically bound by two nucleolar proteins, Nucleolin (NCL) and Nucleophosmin (NPM). Using imaging, we found that the MALAT1 rG4s facilitate the localization of both NCL and NPM to nuclear speckles, and specific G-to-A mutations that disrupt the rG4 structures compromised the localization of both NCL and NPM in speckles. In vitro biophysical studies established that a truncated version of NCL (& UDelta;NCL) binds tightly to all three rG4s. Overall, our study revealed new rG4s within MALAT1, established that they are specifically recognized by NCL and NPM, and showed that disrupting the rG4s abolished localization of these proteins to nuclear speckles

Carbohydrate-based polyester and amino acid polyester photocrosslinker and their resin formulation for 3D printing applications - Kamble, Ganesh N.; Joshi, Dheeraj Chandra; Gavhane, Utreshwar A.; Asha, S. K. (Chemistry-An Asian Journal, 2025)
Fully bio-based polyester was designed and synthesized using the carbohydrate-based diol 2,4:3,5-di-O-methylene-D-mannitol (Manx) and dimethyl ester of 2,3:4,5-di-O-methylene-galactaric acid (Galx). Photocurable resin formulations were prepared by incorporating up to 15 wt% of the carbohydrate polyester into hydroxyl ethyl methacrylate (HEMA) along with polyacrylamide crosslinker derived from L-glutamic acid. Complex 3D structures with good shape fidelity could be 3D printed using these novel polyester resin formulations. The incorporation of the carbohydrate polyester improved the glass transition temperature of the 3D-printed objects. Enzymatic erosion studies conducted using esterase enzyme revealed a higher degradation rate for the 3D-printed films containing the carbohydrate polyester. The hydrolytic degradation analysis conducted in both acidic and basic environments revealed that the 3D-printed polymer network exhibits stability and resilience in acidic conditions, while it undergoes complete degradation in basic conditions. This finding underscores the possibility of tailoring degradation processes under regulated circumstances.
Keywords: 3D printing; Amino acid; Carbohydrate polyester; Enzymatic degradation; Resin formulation